Production of high fibre bread from oil palm pericarp fibre / Haslina Kamarun Zaman - Kamarun Zaman, Haslina (Faculty of Applied Sciences, 2008)
The oil palm fibre may provide potential alternative source of revenue for oil palm industries and the abundance of this raw materials lead to this study of incorporated it into the production of high fibre bread. The aims of this study were to evaluate the feasibility of producing high fibre bread from oil palm pericarp fibre that leads to an acceptable consumption. Toxicological analysis of BSLA was performed onto the raw material of oil palm pericarp fibre and also the finished product to detect the level of toxicant in different concentration was the major concern. In addition, the heavy metals were detected by using AAS. Several other methods were used in these studies which was sensory evaluation, and also physical and chemical analysis. Physical analysis was to measure the firmness of the bread and determined the fibre content in finished product through chemical analysis. Statistical Package for the Social Sciences (SPSS) was used to analyze the sample by one way ANOVA and Duncan’s to evaluate the significant different between formulations. In addition, the oil palm fibre can be incorporated into production of high fibre bread which was safe to be consuming with an improvement in the bread for better acceptability by the consumers.